Indonesian Consumers and The Green Marketing of Eco-Friendly Personal Care Products - Sudirja, Andrea Renina; Sidik, Bennett Aditya; Handoko, Rudy; Ali, Alavi (Kajian Branding Indonesia, 2023)
This qualitative phenomenological study aims to explore the perceptions of Indonesian consumers towards eco-friendly personal care products and their attitudes towards green marketing strategies, particularly focusing on Love Beauty and Planet, a brand operating under a multinational company. To gather primary insights, this research conducts focus group discussions targeting two different age groups, namely millennials and Gen Z, who actively purchase and consume eco-friendly personal care products through various platforms such as e-commerce and offline stores, while being active users of popular social media platforms. By utilizing this approach, the study aims to provide valuable insights into consumers’ perceptions and attitudes towards eco-friendly personal care products and the effectiveness of green marketing strategies employed by brands like Love Beauty and Planet